2005
DOI: 10.1108/17410400510584901
|View full text |Cite
|
Sign up to set email alerts
|

Developing Indian grain supply chain cost model: a system dynamics approach

Abstract: PurposeThe objective of the present study is to model the total supply chain cost (TSCC) of an Indian grain chain in order to understand and predict the future outcome of each supply chain model in different situations and to devise policies accordingly to reduce TSCC.Design/methodology/approachThe system dynamics (SD) approach is used to model the TSCC model of an Indian grain chain, which takes care of the dynamic interaction of the cost variables.FindingsThe major findings of the paper are the reduced cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Different kinds of cost groupings can be found in the literature. Bowersox and Closs (1996), Chen (1997), Sachan et al (2005) and Byrne and Heavey (2006) have presented similar definitions. These definitions use, for example, different terms for the same thing, such as ''Production cost'' (Chen, 1997) and ''Manufacturing cost'' (Bowersox and Closs, 1996).…”
Section: Logistics Cost Versus Supply Chain Costmentioning
confidence: 74%
See 1 more Smart Citation
“…Different kinds of cost groupings can be found in the literature. Bowersox and Closs (1996), Chen (1997), Sachan et al (2005) and Byrne and Heavey (2006) have presented similar definitions. These definitions use, for example, different terms for the same thing, such as ''Production cost'' (Chen, 1997) and ''Manufacturing cost'' (Bowersox and Closs, 1996).…”
Section: Logistics Cost Versus Supply Chain Costmentioning
confidence: 74%
“…Chen (1997) says that SCC can be divided into five categories: Production cost, Transportation cost, Warehousing cost, Inventory carrying cost and Internal material handling cost. Sachan et al (2005) have studied the total SCC in the Indian grain chain. They define the total Supply Chain Cost as the sum of the farmer's price, total additional cost, total mark-up and total wastage.…”
Section: Logistics Cost Versus Supply Chain Costmentioning
confidence: 99%
“…We found few articles addressing this severe problem in international journals or conferences. After summarizing India"s current grain supply chains and how the spoilage and mark-up rates accumulated through the chain, Sachan et al [7] and Sachin et al [8] proposed, with a System Dynamics approach, cost models for three supply-chain-integration alternatives for grains (namely cooperative supply chain model, collaborative supply chain model and contract farming). Few Indian journal or conference articles about grain supply chains were found, e.g., [9,10].…”
Section: September 2011mentioning
confidence: 99%
“…In a study by Sachan, Sahay and Sharma (2005), on developing a supply chain cost model in the Indian agricultural sector, the use of the system-dynamics grain supply chain model was suggested to reduce costs supply chain-wide. Research by Wu (2005) in the United States automatic test equipment industry found that architectural costs are hierarchically organised and interrelated.…”
Section: Introductionmentioning
confidence: 99%